(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
A. Guerra (Palaeohispanica 3) related to the toponym O Gerês/O Xurés the following ones: the name of the mansio Aquis Ocerensis, the toponym Estrada da Geira (< *Ogeira) and the goddess Ocaera. In this work I try to examine the morphologic and phonetic requisites that involves the identification of Ocerensis and the form *Ugerense. I reconstructed *Ugerense in a previous work as the primitive form of the toponym, based on the medieval form Ugeres. The toponym *Ogeira, the theonym Ocaera and the epithet of the God Bandi Oge appear also like derivatives of the same root. The epithet Oge is a new indication of the aquatic character of the God.